2022
DOI: 10.48550/arxiv.2202.04142
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stellar populations and star formation histories of the most extreme [OIII] emitters at $z=1.3-3.7$

Mengtao Tang,
Daniel P. Stark,
Richard S. Ellis

Abstract: As the James Webb Space Telescope approaches scientific operation, there is much interest in exploring the redshift range beyond that accessible with Hubble Space Telescope imaging. Currently, the only means to gauge the presence of such early galaxies is to age-date the stellar population of systems in the reionisation era. As a significant fraction of 𝑧 7 βˆ’ 8 galaxies are inferred from Spitzer photometry to have extremely intense [O III] emission lines, it is commonly believed these are genuinely young syst… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
(121 reference statements)
0
2
0
Order By: Relevance
“…Roberts-Borsani et al 2020;Laporte et al 2021). Recently, Tang et al (2022) also reported the presence of evolved stellar populations in extreme [O ] πœ†5007 emitting galaxies at redshifts 1.3βˆ’3.7, where this evolved population can be up to ∼ 40 times more massive than the young starburst associated with the extreme line emission.…”
Section: Under-prediction Of C and Hementioning
confidence: 94%
“…Roberts-Borsani et al 2020;Laporte et al 2021). Recently, Tang et al (2022) also reported the presence of evolved stellar populations in extreme [O ] πœ†5007 emitting galaxies at redshifts 1.3βˆ’3.7, where this evolved population can be up to ∼ 40 times more massive than the young starburst associated with the extreme line emission.…”
Section: Under-prediction Of C and Hementioning
confidence: 94%
“…The strong [O III] emission lines may reveal the extreme conditions of the interstellar medium in a galaxy, and likely associate with low metallicity and high ionizing parameters (McLinden et al 2011;Nakajima et al 2014;Onodera et al 2020;Tang et al 2021b). The extreme [O III] ELGs are often seen as analogs of galaxies in the reionization era (Tang et al 2019;Du et al 2020;Tang et al 2021aTang et al , 2022. And galaxies with large [O III] equivalent widths (EWs; from 200 Γ… to 800 Γ…) are widely used to address the LyΞ± continuum escape fraction in the high-z universe (Fletcher et al 2019;Katz et al 2020;Barrow et al 2020).…”
Section: Introductionmentioning
confidence: 99%